Live high, train low - influence on resting and post-exercise hepcidin levels - Govus, A. D.; Peeling, P.; Abbiss, C. R.; Lawler, N. G.; Swinkels, D. W.; Laarakkers, C. M.; Thompson, K. G.; Peiffer, J. J.; Gore, C. J.; Garvican-Lewis, L. A. (Scandinavian Journal of Medicine & Science in Sports, 2017)
The post-exercise hepcidin response during prolonged (>2 weeks) hypoxic exposure is not well understood. We compared plasma hepcidin levels 3 h after exercise [6 × 1000 m at 90% of maximal aerobic running velocity (vVO2max)] performed in normoxia and normobaric hypoxia (3000 m simulate altitude) 1 week before, and during 14 days of normobaric hypoxia [196.2 ± 25.6 h (median: 200.8 h; range: 154.3-234.8 h) at 3000 m simulated altitude] in 10 well-trained distance runners (six males, four females). Venous blood was also analyzed for hepcidin after 2 days of normobaric hypoxia. Hemoglobin mass (Hbmass) was measured via CO rebreathing 1 week before and after 14 days of hypoxia. Hepcidin was suppressed after 2 (Cohen's d = -2.3, 95% confidence interval: [-2.9, -1.6]) and 14 days of normobaric hypoxia (d = -1.6 [-2.6, -0.6]). Hepcidin increased from baseline, 3 h post-exercise in normoxia (d = 0.8 [0.2, 1.3]) and hypoxia (d = 0.6 [0.3, 1.0]), both before and after exposure (normoxia: d = 0.7 [0.3, 1.2]; hypoxia: d = 1.3 [0.4, 2.3]). In conclusion, 2 weeks of normobaric hypoxia suppressed resting hepcidin levels, but did not alter the post-exercise response in either normoxia or hypoxia, compared with the pre-exposure response.